2015
DOI: 10.1071/ch14130
|View full text |Cite
|
Sign up to set email alerts
|

[18F]Fluorination Optimisation and the Fully Automated Production of [18F]MEL050 Using a Microfluidic System

Abstract: The [ 18 F]radiolabelling of the melanin-targeting positron-emission tomography radiotracer [ 18 F]MEL050 was rapidly optimised using a commercial continuous-flow microfluidic system. The optimal [ 18 F]fluorination incorporation conditions were then translated to production-scale experiments (35-150 GBq) suitable for preclinical imaging, complete with automated HPLC-solid phase extraction purification and formulation. [ 18 F]MEL050 was obtained in 43 AE 10 % radiochemical yield in ,50 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Traditionally, to provide an anhydrous environment, the [ 18 F]fluoride in water is trapped on an anion‐exchange resin (thus also removing radioactive cationic impurities), eluted with a complexing agent in aqueous/organic solvent mixture, and azeotropically dried in a distillation vial. This azeotropic drying is an inefficient and time‐consuming process (>15 mins), during which period, radioactivity (≥10 %) is lost due to the radioactive decay of the fluorine‐18 isotope, as well as non‐specific adsorption of [ 18 F]fluoride to the surface of the distillation vial, leading to lower radiochemical yield (RCY) of the PET radiotracer …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, to provide an anhydrous environment, the [ 18 F]fluoride in water is trapped on an anion‐exchange resin (thus also removing radioactive cationic impurities), eluted with a complexing agent in aqueous/organic solvent mixture, and azeotropically dried in a distillation vial. This azeotropic drying is an inefficient and time‐consuming process (>15 mins), during which period, radioactivity (≥10 %) is lost due to the radioactive decay of the fluorine‐18 isotope, as well as non‐specific adsorption of [ 18 F]fluoride to the surface of the distillation vial, leading to lower radiochemical yield (RCY) of the PET radiotracer …”
Section: Methodsmentioning
confidence: 99%
“…Scheme 1s hows the synthetic route used to synthesize the ligand( 3)a nd complex (5)p recursors, as well as the non-radioactives tandards 4 and 6. N-Oxidation of 1,10-phenanthroline allowed for selective chlorination in the 2-position by the Vilsmeierr eagent to afford 3.N ucleophilica romatic substitution with azeotropically dried fluoride, using 18-crown-6 as ap hase-transfer catalyst, then affordedt he novel 2-fluoro-1,10-phenanthroline ligand (4). Ligands 3 and 4 weret hen chelated to aR e I metal center to attain complexes 5 and 6,r espectively (see the Supporting Information, sections 1.1-1.5).…”
mentioning
confidence: 99%
“…The EtOH was evaporated at 908C for 15 min, before the residue was reconstituted in 1 mL of 10 % ethanolic saline solution as described previously. [16,17] Under these conditions, [ 18 F]FP-TZTP was obtained in 26 AE 10 % RCY (n ¼ 15), with a molar activity of 182 AE 65 GBq mmol À1 at EOS. The entire radiosynthesis was completed in 49 AE 2 min and radiochemical purity was .99 %.…”
Section: Production Of [ 18 F]fp-tztpmentioning
confidence: 99%
“…[15] This customised system has produced a range of 18 F-radiotracers including [ 18 F]CB102, [ 18 F]fluoroalkylcholines, [15] and [ 18 F]MEL050. [16] More recently, it was demonstrated that this system was capable of producing up to three different 18 F-radiotracers sequentially, using the same starting batch of [ 18 F]fluoride. [17] Herein, we discuss the first account of the microfluidic radiolabelling optimisation and production of the muscarinic M 2 imaging agent [ 18 F]FP-TZTP.…”
Section: Introductionmentioning
confidence: 99%
“…Blanch and Wentrup (University of Queensland) describe an investigation into fluorinated carbene reactive intermediates [1] ; Read and co-workers (UNSW) report on the synthesis of novel fluorous surfactant molecules [2] ; Chebib (University of Sydney) and co-workers describe the receptor binding properties of shape-controlled fluorinated GABA analogues [3] ; Matesic and co-workers (Australian Nuclear Science and Technology Organisation) publish a microfluidic protocol for the automated production of 18 F-labelled compounds [4] ; Fraser and Easton (ANU) review the state-of-the-art in biosynthesis approaches to fluorinated peptides and proteins [5] ; Gardiner (CSIRO) reviews the production and commercial applications of fluoropolymers [6] ; Patel and Liu (Macquarie University) describe the synthesis and conformational analysis of fluorinated N-heterocycles [7] ; Harper and co-workers (UNSW) report on the outcomes of S N 2 reactions performed in fluorinated ionic liquid media [8] ; Kassiou and co-workers (University of Sydney) report on the clandestine production of fluorinated recreational drugs [9] ; Hunter and co-workers (UNSW) describe an investigation of fluorinated proline derivatives as enantioselective organocatalysts [10] ; and in an international contribution to this issue, O'Hagan and co-workers (University of St Andrews, UK) report on the fluorovinyl thioether functional group as a novel potential bioisostere of thioester enolates. [11] I sincerely thank all of the authors who have made such fine contributions to this Research Front, as well as the editorial and administrative staff of Aust.…”
mentioning
confidence: 99%